P100 Prime: a web-based HIV risk reduction package for high-risk MSM. (8th June 2017) - Taghinejadi, Neda; Lau, Rebecca; Amrapala, Apichaya; McOwan, Alan; Whitlock, Gary
Abstract : Introduction: Previous work has shown that HIV-negative MSM with the following characteristics attending our service have approximately a 10% chance of acquiring HIV in the following 12 months: rectal bacterial STI, early syphilis infection, previous PEP use. In May 2016, we introduced a web-based support package, PRIME, targeting such high-risk MSM to reduce their HIV risk and encourage more frequent STI testing with the aim of reducing their risk of HIV acquisition to below 5% per year. Methods: Notes review of the first 50 MSM recruited to PRIME between 19 th May 2016 and 7 th June 2016. Results: By the end of 2016, 1531 eligible MSM had joined PRIME. No one had left the service. Of the first 50 PRIME recruits, median age was 32 years. Median number of partners in the preceding 3 months was 5. Indication for joining PRIME was documented in 45 (39 PEP, syphilis 2, bacterial rectal STI 1, 2+ indications, 3). In the preceding 12 months 15 had been diagnosed with chlamydia and 10 with gonorrhoea. To 31 st January 2017, there is 18.8 person-year follow up for these individuals. The average frequency of STI screens per recruit increased from 2.7 to 7.1 per person-year follow-up. During follow-up the number of infections was: 7 chlamydia, 4 gonorrhoea. One individual tested positive for new HIV infection, 10 weeks after joining PRIME. Discussion: The results show it is feasible to engage significant numbers of high risk MSM clinic attendees using online interventions such as PRIME. Early data suggests that the intervention has successfully increased STI screening in this group. Further follow up is required to see if the initiative has achieved its aim of reducing HIV seroconversion to below 5% per year.